The use of rotational thromboelastometry parameters in understanding the coagulopathy following hump-nosed viper (Hypnale spp) bites: a preliminary study - Bhawani Yasassri Alvitigala; Lallindra Viranjan Gooneratne; Iresha Dharmasena; Nuwan Premawardana; Manujasri Wimalachandra; Miyuru Weerarathna; Roopen Arya; Ariaranee Gnanathasan (Tropical Diseases, Travel Medicine and Vaccines, 2023)
Abstract Background Hump-nosed vipers (HNV; Hypnale spp) are one of the medically important venomous snakes in Sri Lanka and South-Western regions of India. The haemostatic dysfunction due to HNV bites is poorly characterized by standard diagnostic tests performed to identify coagulopathy. We aimed to determine the usefulness of rotational thromboelastometry (ROTEM) parameters compared to 20-minute whole blood clotting test (WBCT20) and prothrombin time (PT) in understanding the coagulopathy of HNV bites. Methods Twenty-three HNV snakebite patients in a prospective study of 127 consecutive snakebites were recruited. After recording details of the clinical presentation, PT/international normalized ratio (INR), WBCT20 and ROTEM delta were performed at presentation. Results In this preliminary study, none of the patients had clinically apparent bleeding. Coagulopathy was detected by either WBCT20, INR or ROTEM in 13 HNV patients. Eleven had a coagulopathy detectable by ROTEM (either abnormal EXTEM-CT, INTEM-CT or FIBTEM-MCF) but with negative WBCT20. Of them, only two had prolonged INR values. Two patients had positive WBCT20 but with normal ROTEM and INR values. The remaining 10 patients did not show any coagulopathy either by INR, ROTEM or WBCT20. Conclusion In this preliminary study with small number of sample size, ROTEM parameters appeared to be more sensitive to subtle changes in coagulation compared to WBCT20. The clinical utility of detecting these changes and their usefulness in managing snakebite should be explored further in a larger study.